Unexplored Spaces for Unconventional Paces: Mapping the Colonial and the Body through Aritha van Herk's Work. Issue 5 (20th October 2021) - Pelayo Sañudo, Eva
ABSTRACT: This article analyzes the feminist use of space in Aritha van Herk's self-identified mixed work of geography and fiction. It fundamentally draws on scholarly work that has already focused on the spatial importance in van Herk's fiction. For example, using Marlene Goldman's insights, I examine the crucial role of space in women's search for freedom and the interrogation of traditional gender norms. Her novels primarily explore how new settings – places with different gender-based codes – may result in new roles or options for the female subject. Thus, the author's mapping consists of taking the characters to unusual venues or having them follow unconventional paths in order to expand the borders of the possible for women. Yet, the essay not only approaches the key interplay between place and gender but also aims to highlight the engagement with more recent perspectives that recognize the colonizing aspects of writings about exploration and place. In fact, I will show this colonial awareness informs to a great extent the feminist concern with mapping a new territory. Furthermore, the author is also particularly intent on inscribing the body, which has gathered less critical attention in comparison with the existing analyses of space.